Children's Learning Happiness Attention Deficit Hyperactivity Disorder (ADHD) in Pandemic - Heri Bayu Dwi Prabowo (JPP (Jurnal Pendidikan dan Pembelajaran), 2021)
Corona Virus Disease pandemic (Covid-19) has been galvanizing the world since 2020 until now. One of the impacts on the learning system in schools, for active children will experience obstacles in learning. Researchers used phenomenology approaches to several children at TPQ Baitul Yamin Mosque to understand their learning mentally. The results showed that the existence of pandemics still make them happy by being close to parents, can still overflow expressions through daily activities, and able to increase the intensity of worship through congregational prayers in mosques.